Cross-Species Differential Plasma Protein Binding of MBX-102/JNJ39659100: A Novel PPAR-γ Agonist. (31st July 2008) - Clarke, Holly J.; Gregoire, Francine; Ma, Fang; Martin, Robert; Zhao, Spring; Lavan, Brian E.
Abstract : Drug binding to plasma proteins restricts their free and active concentrations, thereby affecting their pharmacokinetic properties. Species differences in plasma protein levels complicate the understanding of interspecies pharmacodynamic and toxicological effects. MBX-102 acid/JNJ39659100 is a novel PPAR-γ agonist in development for the treatment of type 2 diabetes. Studies were performed to evaluate plasma protein binding to MBX-102 acid and evaluate species differences in free drug levels. Equilibrium dialysis studies demonstrated that MBX-102 acid is highly bound (>98%) to human, rat and mouse albumin and that free MBX-102 acid levels are higher in rodent than in human plasma. Interspecies differences in free drug levels were further studied using PPAR-γ transactivation assays and a newly developed PPAR-γ corepressor displacement (biochemical) assay. PPAR-γ transactivation and corepressor displacement by MBX-102 acid was higher in rat and mouse serum than human serum. These results confirm the relevance of interspecies differences in free MBX-102 acid levels.